Daya efektivitas antibakteri ekstrak daun mint terhadap bakteri : uji bakteri patogen e.coli dan s.aureus yang terdapat pada makanan - Andriani, Nadia Rizki (Maliki Interdisciplinary Journal, 2025)
Mint leaves are known to have potential antimicrobial properties thanks to the content of compounds such as menthol and menthone. the potential of mint leaves as a natural antimicrobial agent that can be used to improve food safety by inhibiting the growth of pathogenic bacteria. Mint leaves have been shown to have strong antimicrobial properties. Compounds such as menthol have the ability to inhibit the growth of bacteria, including pathogenic bacteria such as Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). growth of bacteria such as E. coli and S. aureus from several researchers who revealed. The antibacterial properties of mint leaves show the potential for broad applications in controlling microbial contamination in food, thus potentially increasing food safety for consumers. In addition, mint leaves also have several other benefits in preserving food naturally which can maintain the safety and quality of each food.